Augmentation of myocardial If dysregulates calcium homeostasis and causes adverse cardiac remodeling - Pessah Yampolsky (Nature Portfolio, 2019)
The depolarizing funny current contributing to cardiac pacemaking is upregulated in the myocardium of  failing and infarcted hearts, but whether the current is implied in disease mechanisms is unclear. Here the authors generate HCN4 transgenic mice and show that upregulation of funny current to the levels observed in human heart failure alters calcium homeostasis leading to cardiac remodelling and arrhythmia.